Development and Content Validation of a Patient-Reported Sexual Risk Measure for Use in Primary Care - Fredericksen, Rob J. (J Gen Intern Med, 2018)
BACKGROUND: Patient-provider sexual risk behavior discussions occur infrequently but may be facilitated by high-quality sexual risk screening tools. OBJECTIVE: To develop the Sexual Risk Behavior Inventory (SRBI), a brief computer-administered patient-reported measure. DESIGN: Qualitative item development/quantitative instrument validation. PARTICIPANTS: We developed SRBI items based on patient interviews (n = 128) at four geographically diverse US primary care clinics. Patients were diverse in gender identity, sex, sexual orientation, age, race/ethnicity, and HIV status. We compared sexual risk behavior identified by the SRBI and the Risk Assessment Battery (RAB) among patients (n = 422). APPROACH: We constructed an item pool based on validated measures of sexual risk, developed an in-depth interview guide based on pool content, and used interviews to elicit new sexual risk concepts. We coded concepts, matched them to item pool content, and developed new content where needed. A provider team evaluated item clinical relevance. We conducted cognitive interviews to assess item comprehensibility. We administered the SRBI and the RAB to patients. KEY RESULTS: Common, clinically relevant concepts in the SRBI included number of sex partners; partner HIV status; partner use of antiretroviral medication (ART)/pre-exposure prophylaxis (PrEP); and recent sex without barrier protection, direction of anal sex, and concern regarding HIV/STI exposure. While 90% reported inconsistent condom use on the RAB, same-day SRBI administration revealed that for over one third, all their partners were on ART/PrEP. CONCLUSION: The SRBI is a brief, skip-patterned, clinically relevant measure that ascertains sexual risk behavior across sex, sexual orientation, gender identity, partner HIV serostatus, and partner treatment status, furnishing providers with context to determine gradations of risk for HIV/STI.